2013
DOI: 10.1364/ol.38.000157
|View full text |Cite
|
Sign up to set email alerts
|

Hard x-ray phase contrast imaging using a tabletop Talbot–Lau interferometer with multiline embedded x-ray targets

Abstract: We demonstrate hard x-ray phase contrast imaging (XPCI) using a tabletop Talbot-Lau interferometer in which the x-ray source and source grating are replaced with an x-ray source with multiline metal targets embedded in a diamond substrate. This source realizes an array of linear x-ray sources of a few micrometers width without fabrication difficulty because of the shallow penetration depth of electrons irradiated to the metal targets. This enhances the coherence of x rays from each linear source and allows XPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…During the last few decades several PC-CT methods have been developed, which are based on crystal interferometer [13], free propagation or inline holographic technique [47] or diffraction enhancement [810]. One of the recent developments is differential PC-CT (DPC-CT), based on a grating interferometer [1121]. DPC-CT has first been implemented at x-ray synchrotron radiation sources [1114] and recently transferred to lab-based x-ray tube sources [1521].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last few decades several PC-CT methods have been developed, which are based on crystal interferometer [13], free propagation or inline holographic technique [47] or diffraction enhancement [810]. One of the recent developments is differential PC-CT (DPC-CT), based on a grating interferometer [1121]. DPC-CT has first been implemented at x-ray synchrotron radiation sources [1114] and recently transferred to lab-based x-ray tube sources [1521].…”
Section: Introductionmentioning
confidence: 99%
“…One of the recent developments is differential PC-CT (DPC-CT), based on a grating interferometer [1121]. DPC-CT has first been implemented at x-ray synchrotron radiation sources [1114] and recently transferred to lab-based x-ray tube sources [1521]. Several experimental studies reported in the literature have demonstrated that DPC-CT offers improved soft-tissue contrast compared to the conventional absorption-contrast CT [1617, 19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…In the hard x-ray regime, phase contrast imaging is the primary contrast-generating mechanism because that samples generally are more transparent. A variety of phase sensitive techniques have been implemented for lens-based full-field x-ray microscopes including both Zernike phase contrast 7-12 and others promising phase contrast imaging methods [13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…1(b)] [4]. When electrons were irradiated on the targets, x rays were generated by both the metal multilines and the diamond substrate.…”
mentioning
confidence: 99%
“…We can easily fabricate multiline targets of less than 10 μm by conventional photolithography and reactive ion etching (RIE) processes. In our previous study, we fabricated an array of linear x-ray sources of 5 μm line width and achieved XPCI with high power efficiency and source-detector distances for Cu and Mo targets of 45-90 cm, respectively [4].…”
mentioning
confidence: 99%